Oxidation of azidoalkyl furans. Issue 50 (14th December 2016) - Kazancioglu, Mustafa Zahrittin; Akin Kazancioglu, Elif; Secen, Hasan; Altundas, Ramazan
Graphical abstract: Highlights: The oxidation of azidoalkyl furans was achieved with singlet oxygen, m CPBA and NBS. Nitrogen heterocycles bearing a stereocenter and prochiral centers were obtained. The reaction proceeded via furan oxidation, cycloaddition, and nitrogen release. Abstract: The oxidation reactions of various azidoalkyl furans were explored under different conditions to access structurally complex compounds from simple starting materials in an operationally simple, single step reaction. The strategically placed azide functional groups on the alkyl chain of the furan led to the discovery of a new and simple method for the synthesis of five-, six-, and seven-membered nitrogen heterocycles bearing prochiral centers and stereocenters.